Charging type moisture power generation device based on double-layer polymer film and preparation method of charging type moisture power generation device
By using a combination of a double-layer polymer film and an active metal Fe electrode in moisture power generation technology, combined with redox reaction, the problem of performance degradation of moisture power generation technology after long-term operation is solved, achieving high performance and long life It takes into account and improves the reliability and application potential of the device through self-healing functions.
Patent Information
- Application Number
- CN202411166136.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-08-23
AI Technical Summary
The performance of existing moisture power generation technology deteriorates after long-term operation, making it difficult to achieve both long life and high performance.
Using a rechargeable moisture power generation device based on a double-layer polymer film, a bifunctional layer polymer film using polystyrene sulfonic acid/Fe3+ (PSSA/Fe3+) and polydiallyl dimethyl ammonium chloride (PDDA) , combining active metal Fe electrodes and redox reactions to achieve high performance and self-healing functions.
The device can continuously generate electricity in a humid environment, with an output voltage of up to 1.08V, a power density of 5.83μW cm-2, and self-healing through redox reactions when performance deteriorates, achieving 100 operating/charging cycles and over 2080 hours Run stably.
Smart Images

Figure CN119483342A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a rechargeable wet gas power generation device based on a double-layer polymer membrane and a preparation method thereof, belonging to the technical field of wet gas power generation. Background Art
[0002] The depletion of traditional fossil energy and the high demand for energy in the development of human society have prompted researchers to develop green, environmentally friendly and sustainable new energy systems. With the continuous advancement of science and technology, clean energy technologies such as wind energy, geothermal energy, and tidal energy are becoming increasingly mature, but they still face two major challenges: one is that they are relatively restricted by natural conditions and are easily affected by external factors such as terrain and climate; the other is that they need to build large-scale equipment, which is costly and easy to cause environmental damage. In recent years, emerging energy technologies such as solar cells, piezoelectric nanogenerators, triboelectric nanogenerators, and thermoelectric nanogenerators have emerged to convert solar energy, mechanical energy, and thermal energy into electrical energy, thereby alleviating the global energy crisis. However, these technologies are easily restricted by specific weather conditions, and severe vibrations and large temperature differences may cause their power generation performance to decline, affecting further applications. Moisture is ubiquitous on the earth, originating from the large amount of evaporation of water bodies such as lakes, rivers, and oceans. With the deepening of research, scientists have found that water can directly interact with many materials with special structures. As early as 2009, studies have shown that when cellulose, hydrophilic particles, and even metals are exposed to high relative humidity environments, their surfaces may generate excessive charges. The transformation of water from the gaseous state to the adsorbed state is often accompanied by the formation and destruction of hydrogen bonds. In this process, heat exchange, material deformation, ion dissociation, etc. are continuously generated, thereby generating weak electricity. Later, this phenomenon was called moisture-enabled electricity generation (MEG). Compared with other energy conversion technologies, MEG has the characteristics of simple device structure, convenient preparation, excellent performance and green environmental protection. The electricity generated by MEG depends on the ubiquitous moisture in the environment, does not require additional energy input, and breaks the environmental and geographical limitations. These advantages make MEG have great potential in the realization of application and mechanization. In the past few years, the power generation performance of MEG has been improved by several orders of magnitude, enough to power small electronic devices such as electronic calculators, liquid crystal displays, electronic displays and light-emitting diodes. Some of these flexible power generation devices are expected to be used in portable and wearable electronic devices to obtain energy from moisture on the human breath and skin surface, and realize functions such as health monitoring.
[0003] Since the wet gas power generation technology was first proposed, it has made significant progress in expanding power generation materials after less than ten years of development, from the initial carbon-based nanomaterials such as carbon nanoparticles, carbon nanowires, graphene oxide, reduced graphene oxide and graphyne to the current bio-nanomaterials, polymers, metal oxides, etc. The life of wet gas power generation devices has increased from a few hours to hundreds of hours, and the output performance has also increased by several orders of magnitude, which has made significant progress. However, this still cannot meet the power supply for most electronic devices, and the power generation performance needs to be further improved. To obtain higher MEG output power, a higher relative humidity and more and higher-valent carriers in the power generation material are required. This requires the design of power generation materials with more complex composition and structure. The complex structure of wet electric materials is affected by external factors during the working process, resulting in changes in the chemical and physical properties of the material. For example, the functional groups and asymmetric structures used to generate carriers are easily damaged by the external environment during long-term operation, resulting in loss or collapse. Over time, the performance of MEG will become lower and lower or even completely fail, ultimately making it impossible to commercialize. Therefore, there is a natural conflict between the long life and high performance of MEG. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a rechargeable wet gas power generation device (rMEC) based on a double-layer polymer membrane. The power generation device includes a polystyrene sulfonic acid / Fe 3+ (PSSA / Fe 3+ The excellent output performance of the power generation device is not only due to the high-valent ion concentration difference formed after the double-layer polymer membrane absorbs water and dissociates, but also due to the active metal Fe electrode and PSSA / Fe 3+ The redox reaction between the layers of the rMEC plays a supporting role and greatly improves the power output. 3+ However, when the rMEC is placed in a humid environment containing oxidizing substances, Fe 2+ Can be reoxidized to Fe 3+ , thus forming a new redox reaction and rebuilding the ion concentration gradient. This allows the performance of the rMEC to quickly recover to its initial level, achieving fast charging.
[0005] To achieve the above objectives, the technical solution of the present invention is as follows.
[0006] A rechargeable wet gas power generation device based on a double-layer polymer membrane comprises an active electrode, a double-layer polymer membrane and an inert porous electrode arranged in sequence, wherein the first layer of the double-layer polymer membrane is a mixture of ferric hydroxide, polystyrene sulfonic acid and polyvinyl alcohol, the second layer of the polymer membrane is polydiallyldimethylammonium chloride, the first layer of the polymer membrane is in contact with the active electrode, and the second layer of the polymer membrane is in contact with the inert porous electrode; the material of the active electrode is a metal with a standard electrode potential of -1V to +0.5V, and the material of the inert porous electrode is a metal with a standard electrode potential greater than +1V.
[0007] Preferably, in the first polymer film, based on the total mass of the first polymer film being 100%, the mass fraction of ferric hydroxide is 0.2% to 0.3%, the mass fraction of polystyrene sulfonic acid is 9.8% to 13.8%, and the mass fraction of polyvinyl alcohol is 87% to 90%.
[0008] Preferably, the thickness of the first polymer film is 50-70 microns.
[0009] Preferably, the thickness of the second polymer film is 30-50 microns.
[0010] Preferably, the active electrode material is one or more of chromium, zinc, iron, cadmium, indium, cobalt, nickel, tin, lead, tungsten, molybdenum and copper. More preferably, the active electrode material is one or more of iron, cobalt, nickel, copper and zinc.
[0011] Preferably, the inert electrode is a porous stainless steel plate plated with a gold, platinum or iridium film, and the gold film is in contact with the second polymer film.
[0012] A method for preparing a rechargeable wet gas power generation device based on a double-layer polymer membrane, the method steps comprising:
[0013] (1) Add ferric hydroxide powder to polystyrene sulfonic acid (PSSA) aqueous solution, stir and react for 48 to 72 hours, centrifuge and collect the supernatant after the reaction to obtain PSSA / Fe 3+ Solution; PSSA / Fe 3+ After the solution is evenly mixed with the polyvinyl alcohol aqueous solution, it is coated on the substrate and dried to obtain a first layer of polymer film on the substrate;
[0014] (2) uniformly spraying a polydiallyldimethylammonium chloride (PDDA) solution on the surface of the first polymer film, drying at 55-70° C. for 15-30 min to form a second polymer film, thereby obtaining a double-layer polymer film;
[0015] (3) The double-layer polymer membrane is placed between the active electrode and the inert porous electrode, with the first layer of the polymer membrane in contact with the active electrode and the second layer of the polymer membrane in contact with the inert porous electrode, thereby obtaining a rechargeable wet gas power generation device based on the double-layer polymer membrane.
[0016] Preferably, in step (1), the concentration of the polystyrene sulfonic acid (PSSA) aqueous solution is 30-35 wt%, the concentration of the polyvinyl alcohol aqueous solution is 10-15 wt%, and the PSSA / Fe 3+ The mass ratio of the solution to the polyvinyl alcohol aqueous solution is 7:1 to 15:1.
[0017] Preferably, in step (1), drying is performed at 45-50° C. for 4-5 hours.
[0018] Beneficial Effects
[0019] The present invention provides a rechargeable wet gas power generation device based on a double-layer polymer membrane. Through moisture evaporation and redox reaction, the battery can generate electricity in a humid environment, and self-repair through redox reaction when the performance decreases, thereby achieving a charging effect. When the double-layer polymer membrane absorbs moisture, the iron ions in the PSSA layer interact with water molecules to form a double electric layer. The evaporation of water on the surface of the material drives the unidirectional migration of counter ions on the double electric layer to generate current. At the same time, the iron electrode undergoes a redox reaction with the PSSA layer, which increases the ion concentration difference of the battery and enhances the output performance of the battery. When it is placed in a humid environment containing oxidizing substances, Fe 2+ Reoxidized to Fe 3+ , rebuild the ion concentration gradient, restore battery performance and achieve charging effect.
[0020] The present invention provides a rechargeable wet gas power generation device based on a double-layer polymer membrane. The rechargeable wet gas battery combines wet gas power generation and redox reaction. A single battery can provide an output voltage of up to 1.08V and exhibits an excellent power density of 5.83μW cm -2 . When the performance of the rechargeable wet gas battery decreases due to the consumption of internal carriers, the reversibility of the redox reaction can be used for self-repair to achieve a charging effect. The rechargeable wet gas battery can complete 100 working / charging cycles continuously and operate stably for more than 2080 hours. In addition, exposing the battery with degraded performance to industrial wastewater / gas containing oxidizing substances can also achieve a charging effect, promoting the reuse of waste resources. The introduction of the environmentally friendly rechargeable wet gas battery not only overcomes the defect that traditional wet gas power generation devices cannot be reused, but also provides a new opportunity for the further iteration and upgrading of wet gas power generation technology. This breakthrough will bring creative changes to the field of clean energy and inject new vitality into the construction of a green and sustainable energy system. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of the preparation of the double-layer polymer film in Example 1.
[0022] Figure 2 Schematic diagram of the structure of the rMEG device in Example 1.
[0023] Figure 3 This is a physical picture of the rMEC device in Example 1.
[0024] Figure 4 This is a SEM image of the cross section of the double-layer polymer film of Example 1.
[0025] Figure 5 This is a curve diagram of the voltage generated by the rMEG device in Example 1 versus time.
[0026] Figure 6 This is a physical picture of the integrated rMEG device in Example 2 lighting a small light bulb.
[0027] Figure 7 This is a real picture of the rMEG device being charged by oxidizing solution vapor and a diagram of the output voltage in Example 3.
[0028] Figure 8 This is a physical picture of the oxidizing solution in Example 3.
[0029] Fig. 9 It is a comparison chart of open circuit voltage and short circuit current in Example 1, Example 4 and Comparative Examples 1-2.
[0030] Fig.10 This is a line graph of power density versus load resistance in Example 5.
[0031] Fig.11 The voltage change diagram of 100 charge and discharge cycles in Example 6 and the voltage recovery rate after each charge. DETAILED DESCRIPTION
[0032] The present invention will be further described in detail below in conjunction with specific embodiments.
[0033] The test equipment used in the following examples is as follows:
[0034] Digital SourceMeter: Keithley (2612).
[0035] Scanning electron microscope: SUPRA 55, Zeiss.
[0036] High purity gold target: 99.999%, Zhongnuo New Materials (Beijing) Technology Co., Ltd.
[0037] Example 1
[0038] Step 1: Weigh 5 g of 30 wt% polystyrene sulfonic acid (PSSA, molecular weight 75,000) solution in a 250 ml beaker and dilute it with 25 g of deionized water. Then weigh 0.1 g of iron hydroxide powder and add it to the diluted PSSA solution. Stir and react for 48 hours.
[0039] Step 2: Place the reaction solution into a centrifuge at 4000 rpm min -1 The mixture was centrifuged at a speed of 30 minutes to remove excess unreacted iron hydroxide powder. 10 g of polyvinyl alcohol powder was weighed in a 250 ml beaker, and 90 g of deionized water was added thereto. The mixture was stirred at 80° C. for 1 hour to obtain a 10 wt% polyvinyl alcohol (molecular weight 30,000-45,000) solution.
[0040] Step 3: After the supernatant after centrifugation is evenly mixed with the polyvinyl alcohol solution in a mass ratio of 10:1, 6 ml is slowly dripped into a culture dish and dried in an oven at 45°C for 4 hours to obtain the first layer of polymer film.
[0041] Step 4: Figure 1 As shown (because PVA chain is the skeleton, PSSA / Fe 3+ Attached to the surface of the PVA chain, PVA does not actually participate in the chemical reaction and moisture power generation process, so PVA is not shown): On the basis of the first layer of film, a 35wt% polydiallyl dimethyl ammonium chloride solution (PDDA, molecular weight 450) is evenly sprayed in small amounts and multiple times with a spray gun, and quickly dried at 60°C in a blower dryer for 20 minutes to prevent the two components in the double-layer polymer film from interpenetrating. The spray thickness of the second layer of polymer film is controlled by measuring with a film thickness meter, and finally a double-layer polymer film is obtained.
[0042] Step 5: A layer of gold film was plated on a stainless steel plate with holes (2 cm × 2 cm, hole diameter 0.8 mm) by ion sputtering as an inert porous electrode, and another iron sheet (2 cm × 2 cm, without holes) was taken as an active electrode. The double-layer polymer film was placed between the inert porous electrode and the active electrode. The first layer of film (PSSA / Fe 3+ ) is in contact with the iron electrode, and the second film (PDDA) is in contact with the inert electrode. Figure 2 The sandwich structure shown.
[0043] Wet gas power generation devices such as Figure 3 Assembly shown: The entire device consists of a nitrogen cylinder, a wide-mouth bottle, deionized water and a conduit. Nitrogen flows into deionized water from the hose on the right. When the gas escapes from the hose on the left, it carries a large amount of water molecules to form moisture.
[0044] Figure 4From the SEM image of the double-layer membrane interface, it can be seen that the double-layer polymer composite membrane was successfully prepared. The polymer membrane composed of two functional layers with clear boundaries laid a good foundation for the subsequent establishment of ion concentration gradient.
[0045] Figure 5 The figure shows the change of the release voltage of the moisture power device over time when it is exposed to moisture with a relative humidity of 85%. When constructing the moisture power device, it can be guaranteed that the discharge voltage of a single device is at most around 1.2V. The inset shows the voltage output curve of the moisture power device during the initial working time. Figure 5 It shows that the wet gas power generation device can generate electricity continuously for more than 24 hours and the output voltage is stable above 0.65 V. This shows that the rMEG device prepared by this method has good electrical output performance.
[0046] Example 2
[0047] In this example, five rMEC device units prepared in Example 1 are connected in series to power a 0.1W LED bulb, which is continuously exposed to a humid environment for 24 hours. After the brightness of the bulb becomes significantly dim, it is exposed to an oxidative humid environment for charging. After charging for 30 minutes, the brightness of the bulb is restored to the brightness of the bulb just exposed to the humid environment. Figure 6 shown.
[0048] Example 3
[0049] In this embodiment, nitric acid, potassium permanganate and hypochlorous acid are prepared into an aqueous solution of a certain concentration to simulate industrial wastewater, and the solution vapor containing oxidizing substances is directed toward the rMEG device prepared in Example 1 to charge the rMEG device.
[0050] Figure 8 To simulate the oxidizing solution of industrial wastewater, Figure 7 After 20 hours of continuous discharge, the output voltage of the rMEG device has dropped significantly. After a brief exposure to moisture containing oxidative substances, the output voltage returns to a higher level.
[0051] Example 4
[0052] In this embodiment, the active electrode is copper, and the rest is the same as in Embodiment 1.
[0053] Comparative Example 1
[0054] In this comparative example, the active electrode is replaced with silver, and the rest is the same as in Example 1.
[0055] Comparative Example 2
[0056] In this comparative example, the active electrode is replaced by an inert electrode of gold, and the rest is the same as in Example 1.
[0057] After the wet gas power generation devices prepared in Examples 1, 4 and Comparative Examples 1-2 were soaked, their short-circuit current and open-circuit voltage were measured using a digital source meter. The results are as follows: Fig. 9 shown.
[0058] from Fig. 9 It can be seen that the rechargeable wet gas power generation devices prepared by the method of the present invention in Examples 1 and 4 can generate current and voltage during use. The change of the active electrode in Comparative Example 1 leads to the disappearance of the redox reaction, affecting the increase of voltage and the movement of carriers, thereby reducing the generated voltage and current. Comparative Example 2 does not use an active electrode, resulting in the smallest output voltage and current in the series of experiments.
[0059] Example 5
[0060] The rechargeable wet gas power generation device prepared in Example 1 was connected in series with an adjustable resistor, and the real-time current and voltage were measured using a Keithley (2612) digital source meter while changing the resistance. The test results are as follows: Fig.10 The load resistance is 10 6 The power density is maximum when Ω.
[0061] Example 6
[0062] The rechargeable wet gas power generation device prepared in Example 1 was placed in a wet environment to generate electricity for one hour, and then transferred to a wet environment containing an oxidizing substance to charge for one hour. The reciprocating cycle was carried out using a Keithley (2612) digital source meter for real-time measurement. Fig.11 It is shown that the voltage recovery rate is maintained close to 100% during 100 charge and discharge cycles within 2080 hours, proving that the device has a good cycle life.
[0063] In summary, the invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the invention shall be deemed to be within the protection scope of the invention.
Claims
1. A rechargeable wet gas power generation device based on a double-layer polymer membrane, characterized in that: It includes an active electrode, a double-layer polymer film and an inert porous electrode arranged in sequence, wherein the first layer of the double-layer polymer film is a mixture of ferric hydroxide, polystyrene sulfonic acid and polyvinyl alcohol, the second layer of the polymer film is polydiallyldimethylammonium chloride, the first layer of the polymer film is in contact with the active electrode, and the second layer of the polymer film is in contact with the inert porous electrode; the material of the active electrode is a metal with a standard electrode potential of -1V to +0.5V, and the material of the inert porous electrode is a metal with a standard electrode potential greater than +1V.
2. A rechargeable wet gas power generation device based on a double-layer polymer membrane as claimed in claim 1, characterized in that: In the first polymer film, based on the total mass of the first polymer film being 100%, the mass fraction of ferric hydroxide is 0.2% to 0.3%, the mass fraction of polystyrene sulfonic acid is 9.8% to 13.8%, and the mass fraction of polyvinyl alcohol is 87% to 90%.
3. A rechargeable wet gas power generation device based on a double-layer polymer membrane as claimed in claim 1 or 2, characterized in that: The thickness of the first polymer film is 50-70 microns.
4. A rechargeable wet gas power generation device based on a double-layer polymer membrane as claimed in claim 1 or 2, characterized in that: The thickness of the second polymer film is 30-50 microns.
5. A rechargeable wet gas power generation device based on a double-layer polymer membrane as claimed in claim 1 or 2, characterized in that: The active electrode material is one or more of chromium, zinc, iron, cadmium, indium, cobalt, nickel, tin, lead, tungsten, molybdenum and copper.
6. A rechargeable wet gas power generation device based on a double-layer polymer membrane as claimed in claim 5, characterized in that: The active electrode material is one or more of iron, cobalt, nickel, copper and zinc.
7. A rechargeable wet gas power generation device based on a double-layer polymer membrane as claimed in claim 1 or 2, characterized in that: The inert electrode is a porous stainless steel plate plated with a gold, platinum or iridium film, and the gold film is in contact with the second polymer film.
8. A method for preparing a rechargeable wet gas power generation device based on a double-layer polymer membrane according to any one of claims 1 to 7, characterized in that: The method steps include: (1) Add ferric hydroxide powder to polystyrene sulfonic acid aqueous solution, stir and react for 48 to 72 hours, centrifuge and collect the supernatant after the reaction to obtain PSSA / Fe 3+ Solution; PSSA / Fe 3+ After the solution is evenly mixed with the polyvinyl alcohol aqueous solution, it is coated on the substrate and dried to obtain a first layer of polymer film on the substrate; (2) spraying a polydiallyldimethylammonium chloride solution uniformly on the surface of the first polymer film, drying at 55 to 70° C. for 15 to 30 minutes to form a second polymer film, thereby obtaining a double-layer polymer film; (3) The double-layer polymer membrane is placed between the active electrode and the inert porous electrode, with the first layer of the polymer membrane in contact with the active electrode and the second layer of the polymer membrane in contact with the inert porous electrode, thereby obtaining a rechargeable wet gas power generation device based on the double-layer polymer membrane.
9. The method for preparing a rechargeable wet gas power generation device based on a double-layer polymer membrane according to claim 8, characterized in that: In step (1), the concentration of the polystyrene sulfonic acid aqueous solution is 30-35wt%; the concentration of the polyvinyl alcohol aqueous solution is 10-15wt%; PSSA / Fe 3+ The mass ratio of the solution to the polyvinyl alcohol aqueous solution is 7:1 to 15:
1.
10. The method for preparing a rechargeable wet gas power generation device based on a double-layer polymer membrane according to claim 8, characterized in that: In step (1), drying is performed at 45-50° C. for 4-5 hours.
Citation Information
Patent Citations
Axial heterostructure nano array, preparation method thereof and application
CN112435860A
Moisture enabled electric power generation materials and device
US20220407436A1
Cited By
Seepage management and self-power generation double-bionic wound dressing as well as preparation method and application thereof
CN120733098A